RESEÑA de : Davies, Wendy. Acts of Giving: Individual, Community, and Church in Tenth-Century Christian Spain. Oxford: Oxford University Press, 2007. - Castro Correa, Ainoa (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2015)
RESEÑA de : Davies, Wendy. Acts of Giving: Individual, Community, and Church in Tenth-Century Christian Spain. Oxford: Oxford University Press, 2007.